KUALITAS PELAYANAN PENDAFTARAN TANAH PADA KANTOR PERTANAHAN KOTA PALU - Rahab, Rahab (Katalogis, 2015)
This Research Target is to know and analyse the quality of service land registry at Office of Land; Ground of Palu Town.  By Using Research Type Qualitative hence informan selected in this research five of people. Data collecting use the technique interview and documentation. Technique analyse the data used  that is ( 1) Editing Data ( 2) Data Subdividing ( 3) Interpretation Mean the Data and ( 4) Withdrawal of Conclusion and Suggestion. Result of Research (1) Quality of Service Land Registry in Office of Land;Ground of Palu Town seen from mainstay factor not yet walked better this matter is seen from time duration still in getting land;ground certificate and result of interview with informan.(2) Quality of Service  land registry in Office of Land;Ground of Palu Town seen from factor Responsivitas not yet walked better this matter is seen by that society still visit upon the office of Land;Ground of Hammer Town, also supported by result of interview with the informan conducted by field. ( 3) Quality of Service of land registry in Office of Land;Ground of Hammer Town seen from Guarantee factor have walked better (4) Quality of Service  land registry  Office of Land;Ground of Palu Town seen from empathy factor have walked better and ( 5) Quality of Service  land registry in Office of Land;Ground of Palu Town seen from Direct Evidence factor have walked better.